Early feminists of colonial India : Sarala Devi Chaudhurani and Rokeya Sakhawat Hossain - Ray, Bharati (New Delhi ; New York : Oxford University Press, 2002)
With reference to Bengal, India.
Includes bibliographical references (p. [155]-168) and index.
Keywords: Chaudhurani, Sarala Devi, -- 1872-1945.; Rokeẏā, -- Begama, -- 1880-1932.; Feminists -- India -- Bengal -- Biography; Women -- India -- Bengal -- Social conditions